2011
DOI: 10.1111/j.1467-9566.2010.01284.x
|View full text |Cite
|
Sign up to set email alerts
|

Actions speak louder than words: the embodiment of trust by healthcare professionals in gynae‐oncology

Abstract: Trust is vital for quality healthcare outcomes, yet existing research neglects the 'embodiedness' of the interactions on which trust is based. This article draws on qualitative data from semi-structured interviews with cervical cancer patients. The significance of body work in winning or, on occasions, undermining trust emerged as a key theme within the responses. Interpretations of professionals' verbal and non-verbal presentations-of-self were often mutually reinforcing and intrinsically linked -forming a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 30 publications
1
29
0
Order By: Relevance
“…We might therefore typify the risk management approach as characterised by a particular form of rationality, through which 'explicit knowledge' (Lam, 2000) is applied in an aggregated and calculative manner (Zinn, 2008). In contrast, trust can be described as invoking a more embodied and tacit manner of working with uncertainty when vulnerable (Barbalet, 2009;Brown et al, 2011). Unlike risk and trust, hope is (shaped amidst but) not dependent upon knowledge from the past, hence Zinn's (2008) 'non-rational' label.…”
Section: Towards a Post-formal Approachmentioning
confidence: 92%
“…We might therefore typify the risk management approach as characterised by a particular form of rationality, through which 'explicit knowledge' (Lam, 2000) is applied in an aggregated and calculative manner (Zinn, 2008). In contrast, trust can be described as invoking a more embodied and tacit manner of working with uncertainty when vulnerable (Barbalet, 2009;Brown et al, 2011). Unlike risk and trust, hope is (shaped amidst but) not dependent upon knowledge from the past, hence Zinn's (2008) 'non-rational' label.…”
Section: Towards a Post-formal Approachmentioning
confidence: 92%
“…In the context of gynae-oncology, one study claimed that trust is likely to vary across different clinical settings as they relate trust to "a particular physiological, emotional, clinical, cultural and gendered context of body work" (p. 292) and reported that gender may influence the embodied phenomenon of trust in patients with cervical cancer [42]. For those with schizophrenia, the act of bringing service to the patient in a caring manner may result in fostering trust.…”
Section: Trust Related To Situations Roles and Competencementioning
confidence: 99%
“…Heath (1986), for example, has explored the ways in which both clinicians and patients use their gaze and body language to indicate recipiency and to prompt the other to talk. Brown and colleagues (2011) have explored how clinicians use their bodies to convey information to patients, usually as a complement to verbal language, within the context of gynae‐oncology. For many of the patients included in the study, whether or not they trusted a clinician depended a great deal on the clinician's bodily actions and gestures.…”
Section: The Clinician‐body Space and Knowledge Production In Medicinementioning
confidence: 99%